O efeito Casimir dinâmico e decoerência - Céleri, Lucas Chibebe (Universidade Federal de São Carlos, 2008)
In this thesis we first demonstrate that the inevitable action of the environment can be substantially weakened when considering appropriate nonstationary quantum systems. Beyond protecting quantum states against decoherence, an oscillating frequency can be engineered to make the system-reservoir coupling almost negligible. Differently from the program for engineering reservoir and similarly to the schemes for dynamical decoupling of open quantum systems, our technique does not require a previous knowledge of the state to be protected. However, differently from the previously-reported schemes for dynamical decoupling, our technique does not rely on the availability of tailored external pulses acting faster than the shortest time scale accessible to the reservoir degree of freedom. We show, in the domain of cavity quantum electrodynamics, how to engineer such a nonstationary cavity mode through its dispersive interaction with a driven two-level atom. Next, we consider different aspects of the dynamical Casimir effect (DCE) through the derivation of effective Hamiltonians which exhibit the essential features of the phenomenon. We start by investigating the dynamical Casimir effect in a nonideal cavity at finite temperature. We first compute a general expression for the average number of particle creation, applicable for any law of motion of the cavity boundary. We also compute a general expression for the linear entropy of an arbitrary state prepared in a selected mode, also applicable for any law of motion of the cavity boundary. As an application of our results we have analyzed both the average number of particle creation and linear entropy within a particular oscillatory motion of the cavity boundary. On the basis of these expressions we develop a comprehensive analysis of the resonances in the number of particle creation in the nonideal dynamical Casimir effect. We also demonstrate the occurrence of resonances in the loss of purity of the initial state and estimate the decoherence times associated with these resonances. We also consider the dynamical Casimir effect for a massless scalar field, under Dirichlet boundary conditions, between two concentric spherical shells. We obtain a general expression for vii the average number of particle creation, for an arbitrary law of radial motion of the spherical shells, using two distinct methods: by computing the density operator of the system and by calculating the Bogoliubov coefficients. We apply our general expression to breathing modes: when only one of the shells oscillates and when both shells oscillate in or out of phase. We also analyze the number of particle production and compare it with the results for the case of plane geometry. Finally, we analyze the action of the gravitational field on the dynamical Casimir effect. We consider a massless scalar field confined in a cuboid cavity placed in a gravitational field described by a static and diagonal metric. With one of the plane mirrors of the cavity allowed to move, we compute the average number of particles created inside the cavity by means of the Bogoliubov coefficients computed through perturbative expansions. We apply our result to the case of an oscillatory motion of the mirror, considering a weak gravitational field described by the Schwarzschild metric. The regime of parametric amplification is detailed analyzed, demonstrating that our computed result, for the mean number of particles created, is in agreement with associated particular cases in literature.
Keywords: Sistemas não estacionários; Efeito Casimir dinâmico; Decoerência (Decoherence); Gravitação; CIENCIAS EXATAS E DA TERRA::FISICA